The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1002/1097-0142(19951015)76:8<1368::aid-cncr2820760812>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1-antichymotrypsin expression in lung adenocarcinoma and its possible association with tumor progression

Abstract: Background. Alpha‐1‐antichymotrypsin (ACT) is a serine protease inhibitor, expression of which has been shown in various tumor types, but its biologic and clinical implications in tumor tissues are obscure. The authors examined ACT expression in lung adenocarcinoma to determine its clinicopathologic and prognostic significance. Methods. First, reverse transcriptase–polymerase chain reaction (RT–PCR) using oligonucleotide primers specific for ACT and Western blotting and immunohistochemical methods using anti‐A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 30 publications
2
33
0
1
Order By: Relevance
“…By RT-PCR, western blotting, and immunohistochemical methods, AACT synthesis were confirmed in several lung adenocarcinoma cell lines and surgically resected lung adenocarcinomas tissues. The data in clinical materials, combined with results of the previous report that AACT in breast cancer acts as a minor growth factor-like substance, suggested that AACT expression in lung adenocarcinoma also may be associated closely with tumor progression and especially with tumor growth [24]. Combined with our finding, we strongly proposed AACT to be a candidate biomarker for objective and non-invasive diagnosis of NSCLC in urine.…”
Section: Immunohistochemistry Stainingsupporting
confidence: 84%
“…By RT-PCR, western blotting, and immunohistochemical methods, AACT synthesis were confirmed in several lung adenocarcinoma cell lines and surgically resected lung adenocarcinomas tissues. The data in clinical materials, combined with results of the previous report that AACT in breast cancer acts as a minor growth factor-like substance, suggested that AACT expression in lung adenocarcinoma also may be associated closely with tumor progression and especially with tumor growth [24]. Combined with our finding, we strongly proposed AACT to be a candidate biomarker for objective and non-invasive diagnosis of NSCLC in urine.…”
Section: Immunohistochemistry Stainingsupporting
confidence: 84%
“…32 Elevated levels of AAT have been detected in the serum of patients with SCC of the oral cavity. 33 Furthermore, expression of SerpinA3 has been documented in lung adenocarcinoma 34 and in tandem with SerpinA1 in human leukocyte antigen-positive cervical carcinoma. 35 In this study, in an effort to discover novel biomarkers for the progression of cutaneous SCC, we analyzed expression of the entire serpin family in skin SCC cells using an oligonucleotide-based microarray technique.…”
Section: Discussionmentioning
confidence: 99%
“…AAT is known to down regulate tumor necrosis factor-induced apoptosis, elevated levels may therefore promote cell survival and growth of tumors [30]. AACT expression in lung adenocarcinomas was significantly higher in advanced tumors with a higher rate of mitosis [31], and was inversely correlated with shorter disease free survival (DFS) and prognosis. Both Higashiyama, et al [31], and Laursen and Lykkesfeldt [32] concluded that AACT acts as a minor growth factor-like substance in breast cancer, in concordance with its association of poor prognosis in breast cancer patients.…”
Section: Validation Of the Lc-ms Datamentioning
confidence: 99%